Ekstraksi Pewarna Alam Berbahan Kunyit, Nanas Kerang, Lumut, dan Kol Merah Serta Aplikasinya dalam Analisis Fotokimia - Novita Asma Ilahi; Sri Sumardiasih (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
The extraction of natural dyes was carried out on plants with different types of natural dyes. Dye curcumin from turmeric extract (Curcuma longa), chlorophyll dye extraction of alga (Bryophyta), and anthocyanin  dye from red cabbage plants (brassica oleracea) and adam eva plant (tradescantia spathacea). The trituration of each plant was then extracted using ethanol in a ratio of 1 gr: 5 ml with a stirring process for 24 hours. Measurement absorption ability of natural dyes was done using the UV-Visible Lambda Spectrophotometer 25. The peak absorption of dye curcumin was in the wavelength range of 350-500 nm with the peak wave absorbance at 447 nm. The peak absorption of anthocyanin red cabbage dye is in the wavelength range of 327-384 nm. Dye chlorophyll and anthocyanin dye of adam eva plant had wavelength absorbance in the range of visible light and infrared with absorbance peaks at 419 nm and 674 nm.